Serum ferritin and nutritional status: insights from an eating disorders clinic population. Issue 3 (28th November 2013) - Nemba, Kuria; Lewis, Barry; Watson, Hunna; Hoiles, Kimberley; Zhang, Guicheng; Forbes, David
Abstract : Objective: To determine the relationship between serum ferritin and malnutrition in newly assessed patients at a paediatric eating disorders clinic. Design: This was a prospectively assessed clinical cohort study. Setting: Intake assessment clinic of a tertiary eating disorders service for children and adolescents. Methods: Clinical, anthropometric and laboratory features of children and adolescents were systematically measured. The relationship of serum ferritin to other clinical, anthropometric and laboratory measures was determined using linear regression. Results: A total of 121 female patients aged 9.5–17.6 years were included, with body mass index (BMI) z score −5.7 to 1.9 (median −1.3). Using multiple regression, serum ferritin was inversely associated with BMI z score (regression coefficient (β)=−0.234, 95% CI −0.413 to −0.055) and serum insulin-like growth factor 1 (IGF-1) (β=−0.476, 95% CI −0.884 to −0.068) and positively associated with alanine aminotransferase (β=0.357, 95% CI 0.055 to 0.659, controlling for age, pubertal stage and serum iron). Conclusions: In malnourished adolescents with eating disorders increased serum ferritin is associated with lower BMI z score and serum IGF-1.